Flexible Fixation Technique for Subtle Lisfranc Injuries - Ethan R. Harlow MD; Ajit M. Vakharia MD; Mikhail Alexeev MD; Shana Miskovsky MD (SAGE Publishing, 2022)
Background: Subtle Lisfranc injuries represent a primarily ligamentous Lisfranc complex injury involving the Lisfranc ligament and the medial and middle cuneiform ligaments. Static radiographic displacement or dynamic instability of the medial cuneiform and 2nd metatarsal typically warrants operative intervention to prevent chronic functional pain, allow for timely return-to-sport, and mitigate posttraumatic osteoarthritis. Flexible fixation techniques offer a unique solution to the issues seen with transarticular screws, plates, and arthrodesis for ligamentous Lisfranc injuries. Indications: We present the case of a 16-year-old female basketball player with a subtle Lisfranc injury sustained during practice. X-rays show isolated widening of the 1st and 2nd metatarsal bases and dynamic diastasis between the medial and middle cuneiforms. Magnetic resonance imaging (MRI) confirmed a rupture of the plantar Lisfranc ligament. After extensive discussion regarding treatment options, the patient and her family decided to proceed with surgical intervention using a suture anchor and button technique to restore stability to the Lisfranc ligament and intercuneiform complexes. Technique Description: A standardized dynamic examination under anesthesia identifies the extent of the injury. Exposure of the base of the 2nd metatarsal and medial cuneiform is performed. Reduction clamps are applied to restore the intercuneiform relationship and interval between the medial cuneiform and base of 2nd metatarsal. The suture anchor and button construct is placed using fluoroscopic guidance. A final dynamic examination is performed to confirm stability of the construct. Results: Biomechanical studies have shown that flexible fixation maintains physiologic motion about the Lisfranc articulations and has comparable stability to transarticular screws in cadaveric models of isolated Lisfranc ligament insufficiency. Clinical results are limited but demonstrate excellent postoperative functional outcome scores with very few fixation-related complications at 1 to 3 years. Discussion: Flexible fixation techniques for subtle Lisfranc injuries offer unique benefits to transarticular screws, plates, and arthrodesis. We highlight the appropriate evaluation of patients with a suspected subtle ligamentous Lisfranc injury, the surgical technique using a suture button and anchor construct, and review postoperative management and expected outcomes based on the present literature.